'We've shared a lifetime with one another': using reflective visual/verbal journals to develop graduate student relationships. Issue 2 (4th March 2017) - Jesup, Cindy; Lucas, Ivory; Nelms, Rachel; Woodruff, Anthony; Shields, Sara Scott
Abstract: The success of graduate students relies on factors beyond mere cognitive ability, with fostering peer and professional relationships as definitive influences on achievement. Research shows that positive faculty/student relationships are a significant factor in the success of graduate students and that art-making is an effective way to encourage the reflective thinking needed to nurture these relationships. In this article, we examine the relationship between arts informed pedagogy, specifically the use of a visual/verbal journal, and the formation of graduate relationships. The majority of the students in this collaborative inquiry entered their doctoral program at the same time the research class began and all engaged in an artfully imagined introduction to qualitative research course.